The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1016/j.na.2008.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Boundedness and blowup for nonlinear degenerate parabolic equations

Abstract: The author deals with the quasilinear parabolic equation In this paper we consider the following quasilinear parabolic equation:Email address: george chen@cbu.ca (Shaohua Chen).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…r ≥ p + 1 and b < 0, then (3) holds. In fact, by [1] and [11], the positive classical solution exists for all t > 0, ε 0 ≤ u(x, t)/ψ(x) ≤ M , and by [5], the corresponding steady state exists. Under Condition I and II, (3) can be written as…”
Section: Example 2 Consider the Following Equationmentioning
confidence: 98%
See 2 more Smart Citations
“…r ≥ p + 1 and b < 0, then (3) holds. In fact, by [1] and [11], the positive classical solution exists for all t > 0, ε 0 ≤ u(x, t)/ψ(x) ≤ M , and by [5], the corresponding steady state exists. Under Condition I and II, (3) can be written as…”
Section: Example 2 Consider the Following Equationmentioning
confidence: 98%
“…In fact, by [1], the positive classical solution exists and u(x, t)/ ψ(x) ≤ M for some M > 0 and all t > 0. It is easy to see that the corresponding steady state exists.…”
Section: Example 1 Consider the Following Equationmentioning
confidence: 98%
See 1 more Smart Citation
“…Mu et al [12] considered the same problems and obtained similar results. Chen [3] considered the system (1.2) with lower order terms f (u, v, Du) and g (u, v, Dv) and showed that all solutions are bounded if (1 + c 1 ) √ ab < λ 1 and blow up in a finite time if (1 + c 1 ) √ ab > λ 1 , where c 1 > −1 related to f and g. Chen [2] and Chen and Yu [4] also discussed single equations with lower order terms. Li et al [9] investigated the following strong coupled system u t = v p ( u + au) and v t = u q ( v + bv), (1.4) and proved that all solutions are global iff λ 1 min{a, b}.…”
Section: Introductionmentioning
confidence: 99%
“…In this method, we estimate the integral of a ratio of one solution to the other. This method shows successful in proving existence and blowup problems (see [1][2][3][4]). Then we use the method introduced by Li et al [9] to obtain a classical solution to (1.1).…”
Section: Introductionmentioning
confidence: 99%